DESAIN KERANGKA ALAT COUNTING PLANO UNTUK MENGHITUNG HASIL PRODUKSI PADA MESIN PAD 3 PT. XYZ - Syafana, Mohammad Arju; Tsamroh, Dewi Izzatus; Asrizal (LENVARI, 2025)
A jig is a tool or device used to guide or hold an object in the manufacturing or assembly process. Usually, jigs are used to ensure precision and consistency in various types of work, such as drilling, cutting, milling, and assembly. The initial step in making a jig is usually done by creating a design. Design is a creative process that involves planning, arranging, and creating visual or functional elements to achieve certain goals. In a broader context, design is not only limited to the visual arts aspect, but also includes product design, architecture, user experience (UX), as well as communication and graphic design. Tjiwi Kimia Paper Factory, Tbk. PT. Tjiwi Kimia Paper Factory, Tbk. is a paper manufacturing industrial company. PT. Tjiwi Kimia Paper Factory, Tbk has succeeded in becoming the largest paper producing company in Indonesia, even in Asia, with the main product being paper, either in the form of sheet, roll, or has been converted into various kinds of stationery, as well as other products in the form of chemicals, such as NaOH, CaC03, HCl solutions, and others.